Identifying flaws in the GWAS datasets of a published Mendelian randomization study: complementary re-evaluation and suggestion for analytical refinements - Xiang, Jia-Cheng; Xiong, Yi-Fan; Wang, Shao-Gang; Xia, Qi-Dong (Journal of translational medicine, 2024)
Within both gene regions, we discovered a very high posterior probability (100% and 99.14%) supporting Hypothesis 4 (H4), and two co-localized genetic loci (rs117310449 and rs6979218) were identified respectively (Fig. 2B, C, Table 1). SEE PDF] Additionally, the authors extracted eQTL data of brain tissue and whole blood from the GTEX database and identified PVRIG as a risk gene for AD by co-localization analysis. [...]collecting the cis-eQTLs near the PVRIG gene from the eQTLGen database as the exposure (instrumental variables demonstrated in Additional file 4: